The Effect of Prior Experience, Value Consciousness and Brand Image on Repurchase Intention with Sale Proneness Moderation - Mohammad Sulkifli; Adinda Luthfi (Budapest International Research and Critics University, 2022)
This study aims to examine the effect of value awareness, previous experience, and brand image on intention to reuse which is moderated by sale proneness with a case study of Uber's online transportation service. Respondents in this study were men and women throughout Indonesia who had used Uber online transportation services. This study uses a quantitative approach that tests several hypotheses using SEM (Structural Equation Modeling) analysis. This study uses primary data by distributing questionnaires over a certain period which are distributed online. The results of this study indicate that there is no significant effect of the Previous Experience variable on the Brand Image variable but there is a positive and significant influence on the Previous Experience variable on the value awareness variable and there is a positive and significant influence on the Brand Image variable on Repurchase. As well as the positive and significant effect of the interaction between brand image and sale proneness on the repurchase variable.